Internet Access as an Independent Human Right: a Palpable Consequence of the Covid-19 Pandemic? - Bilaney, Kunal; Thampi, Gauri (Kathmandu School of Law Review, 2020)
The onslaught of the COVID-19 pandemic has established a new world order which is heavily reliant upon the internet for public access to health, education, employment, and recreation among other services. Furthermore, the growing dependence on technology has also been crucial in the battle against the pandemic. However, despite the irreplaceable utility of the technology, state practices have remained divergent in this field. While a multitude of nations have recognized internet access as a fundamental right, many nations imposed unjustified restrictions on their citizens during the pandemic and some even failed to provide affordable access to internet facilities, which has proven to be detrimental to the realisation of basic individual rights. As the world makes a transition from a pandemic, the intensifying reliance upon the internet has given rise to a need to recognise access to the internet as an independent human right. In light of the above, the present paper seeks to elucidate how access to the internet has emerged as a necessity in the backdrop of a pandemic and examine how the differing state responses in this context have been violating individual rights. The paper also delves into how internet access is being dealt with under the existing international and domestic regime. Further, the authors attempt to philosophically justify a human right to internet access and politically conceptualise the same, and argue in favour of recognition of internet access as an independent human right under international law.